ANALISIS PENAFSIRAN M. QURAISH SHIHAB TENTANG KARAKTER SEORANG PEMIMPIN DALAM TAFSIR AL-MISBAH - Maskur, Muhammad; Santosa, Sedya (STAI Asy-Syukriyyah, 2023)
This study aims to explore various values ​​of Islamic teachings that can be used as a code of ethics for the character of a leader in the perspective of the Koran according to Tafsir al-Misbah by M. Quraish Shihab. This research is a qualitative research in the form of library research (Library Research). The primary data sources used are the Koran and the book of Tafsir al-Misbah by M. Quraish Shihab. While the secondary data sources used are various scientific literature relevant to the core object of this research. This research includes conceptual research with a philosophical-normative approach. While the nature of this research approach is descriptive-analytic and prescriptive. The results of this study indicate that there are various characters that must be instilled by a leader which can be used as leadership character values, such as Siddiq (honest), Amanah (trustworthy), Tabligh (delivering), and Fatahan (intelligence). Efforts to form leaders with character can be done by cultivating the soul, habituation, exemplary, and the environment.